2015
DOI: 10.14800/ttnd.476
|View full text |Cite
|
Sign up to set email alerts
|

Role of astroglial Kir4.1 channels in the pathogenesis and treatment of epilepsy

Abstract: The inwardly rectifying potassium (Kir) channel subunit Kir4.1 is specifically expressed in brain astrocytes and Kir4.1-containing channels (Kir4.1 channels) mediate astroglial spatial potassium (K + ) buffering. Recent advances in Kir4.1 research revealed that Kir4.1 channels can serve as a novel therapeutic target for epilepsy. Specifically, reduced expression or dysfunction of Kir4.1 channels seems to be involved in generation of generalized tonic-clonic seizures (GTCS) in animal models of epilepsy and pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…The present results suggested that the reduced expression of astrocytic Kir4.1 expression is involved in Lgi1-related epileptic disorders. The dysfunction of astrocytic Kir4.1 channels elevates the extracellular levels and K + and glutamate by suppressing the special K + buffering function of astrocytes, which increases the excitability of neurons [4,5,6,7]. In addition, we previously showed that down-regulation of the Kir4.1 channel expression enhanced the expression of BDNF, which is a key modulator of epileptogenesis, in astrocytes [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present results suggested that the reduced expression of astrocytic Kir4.1 expression is involved in Lgi1-related epileptic disorders. The dysfunction of astrocytic Kir4.1 channels elevates the extracellular levels and K + and glutamate by suppressing the special K + buffering function of astrocytes, which increases the excitability of neurons [4,5,6,7]. In addition, we previously showed that down-regulation of the Kir4.1 channel expression enhanced the expression of BDNF, which is a key modulator of epileptogenesis, in astrocytes [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the spatial potassium (K + ) buffering by astrocytes’ functions is a clearance mechanism of excessive extracellular K + secreted from excited neurons, and is essential for controlling neuronal excitability. If astrocytic K + buffering is disrupted, it increases the extracellular levels of K + and glutamate at the synapses, and causes the abnormal excitation of neurons [4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, astrocytes regulate ion homeostasis and extracellular space volume, metabolize neurotransmitters (e.g., glutamate, GABA, and glycine), and secrete various neuroactive molecules including gliotransmitters [e.g., glutamate, D-serine, adenosine 5 ′ -triphosphate (ATP)], neurotrophic factors [e.g., brain-derived neurotrophic factor (BDNF) and glia-derived neurotrophic factor (GDNF)], and cytokines [e.g., tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β)] (11)(12)(13). Among these functions of astrocytes, a spatial buffering system for potassium ions (K + ) plays an important role in the maintenance of neuronal excitability, which transports excessive extracellular K + secreted from excited neurons to sites with lower K + concentrations (e.g., microcapillaries) (14)(15)(16)(17)(18). This potassium clearance mechanism is primarily mediated by astrocytic inwardly rectifying potassium (Kir) channels containing Kir4.1 subunits (Kir4.1 channels) (16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Among these functions of astrocytes, a spatial buffering system for potassium ions (K + ) plays an important role in the maintenance of neuronal excitability, which transports excessive extracellular K + secreted from excited neurons to sites with lower K + concentrations (e.g., microcapillaries) (14)(15)(16)(17)(18). This potassium clearance mechanism is primarily mediated by astrocytic inwardly rectifying potassium (Kir) channels containing Kir4.1 subunits (Kir4.1 channels) (16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%